Gender, agricultural activities and water governance in rural Tajikistan in midst of male-out migration - Panchali, Saikia (International Water Management Institute, 2017)
Presented by Saikia Panchali (IWMI), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.